TATA KELOLA DANA DESA PADA MASA PANDEMI COVID-19 DI DESA JERINGO KECAMATAN GUNUNGSARI KABUPATEN LOMBOK BARAT NTB - Zahirudin, Ahmad; Rahmandari, Ismi Arifiana; Putra, Sandi Justitia; Zulhadi, Zulhadi; Sujudi, Anis; Arisandy, Rita (Yayasan Panca Bakti Wiyata Pangandaran, 2024)
Jeringo Village is a village located in Gunungsari District, West Lombok Regency. A common problem that occurs is the reallocation of the use of Village Funds in 2020 causing many activities or programs to be abolished. This happened because of the COVID-19 pandemic which required the Village Government to allocate Village Funds for disaster, emergency and urgent village management, namely to handle and overcome the impact of the COVID-19 pandemic, in this case namely for Village Direct Cash Assistance (BLT-Village). ). Based on the description above, the author is interested in conducting deeper research on Village Fund governance during the COVID-19 pandemic and the factors that hinder village fund governance in Jeringo Village, Gunungsari District, West Lombok Regency, West Nusa Tenggara. What is being proposed is how the Village Fund is managed during the COVID-19 pandemic and what are the inhibiting factors in Village Fund governance during the COVID-19 pandemic that occurred in Jeringo Village, Gunungsari District, West Lombok Regency.